2011
DOI: 10.1002/anie.201007269
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III) Complexes Catalyze Deoximations/Transoximations at Neutral pH

Abstract: Reaction of gold trihalides with reducing agents such as thiols, NaBH 4 or hydroxylamine gives gold nanoparticles (Au NPs). [1] In particular, NH 2 OH is used to produce monodisperse colloidal Au NPs by "growing" of smaller particles or to form thin films of Au on glass substrates. [2] Our interest in developing a mild catalytic method for the conversion of nitro/oxime/nitrone groups to carbonyl groups led us to examine first the interaction of gold(III) [3] with simple oximes as a potential deoximation proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…10 In 2011, Burés and Vilarrasa et al reported de-oximation via transoximation using diacetyl as a receptor and AuBr 3 as the catalyst under neutral conditions. 11 In contrast, oximation via catalytic transoximation to prepare the oxime remains poorly developed, despite the existence of transoximases in nature. We were inspired by bio-synthetic pathways to explore catalytic transoximation for several reasons: (1) transoximation could allow the use of stable oximes instead of the dangerous hydroxylamine, (2) some oximes are inexpensively produced industrially by, for example, ammoximation, (3) carbonyl compounds generated from the oxime as byproducts are easily removed by vaporization, (4) depending on the type of byproduct generated, the target oxime can be regenerated industrially using the TS-1 catalyst, 12 and (5) the reaction mechanism of the acid-catalyzed reaction remains poorly understood (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…10 In 2011, Burés and Vilarrasa et al reported de-oximation via transoximation using diacetyl as a receptor and AuBr 3 as the catalyst under neutral conditions. 11 In contrast, oximation via catalytic transoximation to prepare the oxime remains poorly developed, despite the existence of transoximases in nature. We were inspired by bio-synthetic pathways to explore catalytic transoximation for several reasons: (1) transoximation could allow the use of stable oximes instead of the dangerous hydroxylamine, (2) some oximes are inexpensively produced industrially by, for example, ammoximation, (3) carbonyl compounds generated from the oxime as byproducts are easily removed by vaporization, (4) depending on the type of byproduct generated, the target oxime can be regenerated industrially using the TS-1 catalyst, 12 and (5) the reaction mechanism of the acid-catalyzed reaction remains poorly understood (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning, we tried to transform the oxime to an aldehye or a Scheme 2 Synthesis of compound 7. hemi-acetal in the presence of the free 8-OH first and then prepare the lactone by oxidation. However, all attempts with different reagents to convert this oxime in 9 to an aldehyde failed unexpectedly, such as hydrochloric acid, 11 AuBr 3 , 12 NaHSO 3 , 13 Co 2 (CO) 8 , 14 TiCl 4 , 15 and FeCl 3 . 16 (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning, we tried to transform the oxime into an aldehyde or a hemi-acetal in the presence of the free 8-OH first and then prepare the lactone via oxidation. However, all of the attempts with different reagents to convert this oxime in 9 into an aldehyde failed unexpectedly, such as using hydrochloric acid, 11 AuBr 3 , 12 NaHSO 3 , 13 Co 2 (CO) 8 , 14 TiCl 4 , 15 and FeCl 3 include the oxidation of the aldoxime 9 to the nitrile 9C, 18 acid-catalyzed imidate formation, and hydration of imidate. After selective deprotection of the acetate in 10, the resultant primary alcohol was oxidized with IBX at 80 °C to produce compound 12 in a 98% yield while the application of Dess-Martin periodinane at 0 °C afforded the aldehyde in an inferior 71% yield.…”
Section: Resultsmentioning
confidence: 99%
“…3,4-Dihydronaphthalen-2(1H)-one (3a). 3a is a known compound 25 and was prepared in 83% yield (12.1 mg) according to the General Procedure C. 1 H NMR (500 MHz, CDCl 3 ) δ 7.31−7.25 (m, 3H), 7.18 (dd, J = 7.8, 4.1 Hz, 1H), 3.64 (s, 2H), 3.12 (t, J = 6.7 Hz, 2H), 2.66−2.56 (m, 2H).…”
Section: -(2-ethynylphenyl)benzo[b]thiophene (1agmentioning
confidence: 99%